Socioeconomic status in relation to dental caries in Dewanyiah governorate among 12 years old school students - Al-Hassnawi, Amjed K; Al-Waheb, Athraa M (Journal of Baghdad College of Dentistry, 2014)
Background: The socioeconomic is important factor that effect in the severity and prevalence of most predominant and wide spread oral disease named dental caries, since this oral disease effects children, adolescents, adults and elderly peoples especially in developing countries as in Iraq.This survey was aimed to investigate the prevalence and severity of dental caries in relation to socioeconomic status. Materials and Methods: This oral health survey was conducted among primary and secondary school students aged 12 years old in Dewanyiah governorate in Iraq. The total sample composed of 804 (401 boys and 403 girls) selected randomly from different schools in Dewanyiah governorate. Diagnosis and recording of dental caries was assessed according to the criteria described by WHO (1997).The modification of Kuppuswamy's index (1976) was applied for measurement of socioeconomic status.Results: The most of low socioeconomic category was occupied by rural students. The prevalence of dental caries was 70.65 % for the total sample. The mean DMFT was equal to (1.83 Â± 0.068) and DMFS (2.89 Â± 0.126). No significant difference was seen between socioeconomic status and DMFS.Conclusion: A high prevalence of dental caries was recorded. Socioeconomic status may affect dental caries indicating the need for public and health preventive programs among school students.